If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -9 + 8x + -25 = 28 Reorder the terms: -9 + -25 + 3x + 8x = 28 Combine like terms: -9 + -25 = -34 -34 + 3x + 8x = 28 Combine like terms: 3x + 8x = 11x -34 + 11x = 28 Solving -34 + 11x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '34' to each side of the equation. -34 + 34 + 11x = 28 + 34 Combine like terms: -34 + 34 = 0 0 + 11x = 28 + 34 11x = 28 + 34 Combine like terms: 28 + 34 = 62 11x = 62 Divide each side by '11'. x = 5.636363636 Simplifying x = 5.636363636
| 2(-2y+3)+3y=6 | | %x+65+25 | | x=(3x+10) | | 2x^2+8=96 | | 9-9=5x+3x | | f(x)=3x^2-18 | | -3x+5+7x=19 | | 2a-15-5a+1= | | 5x+2=7+x | | 13w-16w=-12 | | -2(2x-4)=8-4x | | 4x-14=3x-6 | | y=9x^2-3x-12 | | Y^2-24+c= | | 13x^2-22=5x^2+26 | | -3(c-1)=-4c-1 | | 4m+4.25=38.25 | | a^2-20a+42=6 | | 6(z+7)-9=27 | | 10(X-3)-20=100 | | 8x+2=16+x | | 4x+6+2x=-6 | | 2a^2-20a+42=6 | | 19b+4-12b=6(3b+19) | | m(x-2)=y-5 | | 13+3(4q-2)=-15+10q-18 | | -5(6x-2)+2=-30x+12 | | -19g=2(-11g+16)-8 | | -20+2(-20t-20)=3(-16t+20) | | 103x+47=1283 | | 2u-2=-4 | | 2j-2j+8j-2j=72 |